Exploration of favourable traits for nitrogen use efficiency in ancient wheat species - Fernando, K.M.C. (2015)
Nitrogen (N) fertiliser is one of the main inputs of intensive wheat cropping systems in the UK. The average application of N fertiliser in the UK for winter wheat was 220 kg N ha-1 in 2011, but typically only 50% of this applied N is taken up by the crop. Breeding crops for high N use efficiency (NUE; grain dry matter yield per unit availability of N from soil and/or fertiliser) while maintaining acceptable yield, is widely accepted as one of the approaches to maximise farmers’ revenue and minimise pollution risk by reducing N fertiliser application. NUE is divided into two components; N uptake efficiency (NUpE; crop N uptake per unit availability of N from soil and/or fertiliser) and N utilisation efficiency (NUtE; grain dry matter yield per crop N uptake). NUE can be improved by improving NUpE and /or NUtE. Targeted integration of favourable traits into breeding programmes needs adequate diversity of the existing genotypes. However, genetic diversity of modern bread wheat is narrowed due to chance hybridisation events during wheat evolution and selective breeding for high yield. Hence, it has become necessary to search for novel sources of genetic variation for NUE. One of the sources could be the ancient wheat species, which provide novel resources of genes to improve NUE of modern bread wheat.